Going Green and Cold: Biosurfactants from Low-Temperature Environments to Biotechnology Applications. Issue 3 (March 2018) - Perfumo, Amedea; Banat, Ibrahim M.; Marchant, Roger
Abstract : Approximately 80% of the Earth's biosphere is cold, at an average temperature of 5°C, and is populated by a diversity of microorganisms that are a precious source of molecules with high biotechnological potential. Biosurfactants from cold-adapted organisms can interact with multiple physical phases – water, ice, hydrophobic compounds, and gases – at low and freezing temperatures and be used in sustainable (green) and low-energy-impact (cold) products and processes. We review the biodiversity of microbial biosurfactants produced in cold habitats and provide a perspective on the most promising future applications in environmental and industrial technologies. Finally, we encourage exploring the cryosphere for novel types of biosurfactants via both culture screening and functional metagenomics. Trends: 'Cold' is becoming 'cool' in microbiology. The cryosphere is becoming more easily accessible to scientific expeditions and is predicted to fuel the discovery of novel natural products. Research on biosurfactants from psychrophilic microorganisms is just beginning but is expected to contribute to the development of sustainable (green) and energy-saving (cold) biotechnologies. New formulations of washing products containing biosurfactants are being developed, which can enable effective detergency at lower temperatures and will help laundry practices to reduce the environmental impact. Advances in unconventional experimental approaches such as functional metagenomics hold great promise for future discovery of entirely new biosurfactant types and producing organisms from cold and extreme environments.